أثر الانفتاح المالي على النمو الاقتصادي في سورية خلال الفترة (1980-2010) - اسماعيل, ليندا; زينب, باسل (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This research aims to examine the impact of de jure and de facto financial openness on the economic growth in Syria during the period (1980-2010). For that purpose, the ordinary least squares method was used. The results reveal that the impact of de jure financial openness is negative but not significant whereas the impact of de facto financial openness is negative and significant. The results also show that the nature of the impact of de facto financial openness on economic growth varies depending on the combination of capital inflows so that debt inflows have a negative impact ongrowth whereas foreign direct inflows have a positive one, but this impact is insignificant in both cases. These results were interpreted by lacking a set of necessary conditions for the financial openness to have a positive impact on the growth in Syria. يهدف هذا البحث إلى دراسة أثر الانفتاح المالي القانوني والواقعي على النمو الاقتصادي في سورية خلال الفترة(1980-2010). لتحقيق هذا الهدف, تم استخدام طريقة المربعات الصغرى العادية.تظهر النتائج أن أثر الانفتاح المالي القانوني سلبي وغير معنوي في حين أن أثر الانفتاح المالي الواقعي سلبي ومعنوي. تظهر النتائج أيضاً أن طبيعة أثر الانفتاح المالي الواقعي على النمو الاقتصادي في سورية تختلف باختلاف تركيبة التدفقات الرأسمالية الداخلة حيث تؤثر تدفقات الدين سلباً على النمو في حين تؤثر تدفقات الاستثمار الأجنبي المباشر إيجاباً, إلا أن هذا الأثر غير معنوي في كلتا الحالتين. وقد تم تفسير النتائج بعدم توفر مجموعة من الشروط (العتبات) الضرورية حتى يحقق الانفتاح المالي أثر ايجابي على النمو في سورية.